Pemanfaatan Instagram Sebagai Sarana Dakwah Bagi Mahasiswa Prodi Komunikasi Dan Penyiaran Islam Stambuk 2018 UIN Sumatera Utara - Nst, Rizky Rahmadani; Samosir, Hasrat Efendi; Yulia, Fatma (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The general purpose of this study was done to find and find the utilization of Instagram as a means of da'wah by communication and broadcasting Islamic structures 2018 UIN Sumatera Utara.The special purpose of this study is to see how students' communication and broadcasting Islam stamuk 2018 in utilizing Instagram as a means of da'wah; Packaging content of da'wah done; Factors support and dilution in jam. This study using qualitative research is described in descriptive form to obtain a deep data description. The data is analyzed, then researchers choose samples from the population based on certain considerations. The data collection method used in this research is by observation, wandsonasi does not directly use WhatsApp to obtain and dig the data clearly and concrete, and documentation containing screenshots (photographs of screenshots during interviews online). The results of the study obtained that: (1) The utilization of Instagram as a means of da'wah for KPI students is considered able to become a debtion message that is relevant to the development of technology and communication. (2) The form of packaging content da'wah uploaded such as image messages, da'wah videos, and caption. (3) supporting factors and inhibitors because the environment or community, is easily accessible, and encouragement from within themselves that feel that conveying the duty task is the duty of every Muslim who has been Baligh. While the factor of its inhibitors because it does not take the time, as well as the lack of science about the da'wah material to be delivered to Mad'u / Audience.